ANALISIS USAHA PADA SKENARIO MODEL PENGEMBANGAN SAPI BERBASIS TANAMAN PANGAN DI KABUPATEN KUPANG - Siviardus Marjaya; Krisna Setiawan (Partner, 2021)
The development of a food crop-based livestock integration model in Kupang Regency is the main solution and development priority. This model is intended to improve food and livestock security. This research is directed to be carried out in an integrated manner (integrated farming system), mutually supporting, strengthening and mutually beneficial (synergy), thereby increasing crop and livestock productivity, efficiently using labor and reducing production costs. The objectives of this research are; 1) develop several alternative scenarios of food crop-based ruminant livestock integration models, 2) produce an effective and efficient food crop-based livestock integration model, 3) analyze the business feasibility of the developed model. The results of the feasibility analysis show that the R/C-ratio in the first scenario is 3.69, the second scenario is 3.16, and the third scenario is 2.28.Keywords: Integration model development, ruminants, food crop base